Expert analysis and insider information in horserace betting: Regulating informed market behavior - John Peirson; Michael A. Smith (University of Kent, Department of Economics, 2008)
We present a new model analyzing the effect of uncertainty faced by bookmakers. It is shown that bettors with inside information or expert analysis decrease the odds set by profit maximizing bookmakers. Data on previously unraced two year old horses and those that have raced previously are used to examine the impact of the greater possibility of insider information on odds bias in relation to unraced horses. The price of a bet on unraced two year olds is found to be on average 15% higher and the effect varies as the probability of winning increases. The latter effect suggests a possible contribution to the favorite-longshot bias and the former shows the importance of insider information in the setting of market prices. The regulation of the use of insider information is discussed in the light of the similar impact of insider information and expert analysis on bookmaker odds.
Keywords: D82; L83; 330; betting; horseracing; insider information; uncertainty; Pferdesport; Glücksspiel; Entscheidung bei Unsicherheit; Sachverständige; Informationsversorgung; Verhalten; Theorie